2014
DOI: 10.1179/1743294414y.0000000261
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of WC coatings evaluated using instrumented indentation technique

Abstract: International audienceInstrumented indentation tests have been conducted on the surface and cross-section of the two WC based coatings obtained by means of high velocity oxygen fuel thermal spray techniques in order to investigate their mechanical properties. The yield strength of the coatings has been determined by means of the Zeng and Chiu model. In addition, the absolute hardness of the coatings has been determined by means of the modified proportional specimen resistance model. Additionally, conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
8
1
Order By: Relevance
“…The maximum von Mises stress value determined for the WC CNT coating is slightly less than that of 2.6 GPa reported previously by La Barbera-Sosa et al. [25] for a HVOF WC-10Co-4Cr coating also found by means of spherical indentation techniques. These authors also reported a maximum von Mises stress value of approximately 1.9 GPa for a WC-12Co, which is quite similar to the one found in the present work for the WC CONV coating.…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…The maximum von Mises stress value determined for the WC CNT coating is slightly less than that of 2.6 GPa reported previously by La Barbera-Sosa et al. [25] for a HVOF WC-10Co-4Cr coating also found by means of spherical indentation techniques. These authors also reported a maximum von Mises stress value of approximately 1.9 GPa for a WC-12Co, which is quite similar to the one found in the present work for the WC CONV coating.…”
Section: Resultscontrasting
confidence: 64%
“…As shown in Figure 5, such a stress is located between approximately 30-40 μm below the coating surface. Therefore, following the approach suggested by La Barbera-Sosa et al [25], in the present work the criterion adopted for determining the coatings yield stress was that of the maximum von Mises stress associated to the smallest load which gives rise to the presence of a visible surface indent. Therefore, the yield stress of the WC CONV and WC CNT coatings can be assume to be approximately 1.8 and 2.2 GPa, respectively.…”
Section: Yield Strength Of the Coatingsmentioning
confidence: 99%
“…The benefits resulting from the application of coatings include, without limitation, the possibility of regeneration and restoring the usable properties of machines and equipment that operate under conditions of abrasive, erosive, and corrosive wear as well as the combination of the beneficial properties of the erosive, and corrosive wear as well as the combination of the beneficial properties of the core with resistance to wear, hardness, and heat. Depending on the source of heat used to melt the coating material, the following types of spraying can be differentiated: wire flame and powder flame spraying, crucible spraying, arc spraying, plasma spraying, and supersonic spraying [6][7][8]. The high-velocity oxygen fuel (HVOF) spraying method is one of the most commonly used methods.…”
Section: Introductionmentioning
confidence: 99%
“…The high velocity oxy-fuel (HVOF) thermal spray process is commonly used for depositing wear resistant coatings and has been successfully used for spraying ceramic coatings such as WC-Co-Cr [1][2][3]. The main applications of this technology are related to internal combustion engine shafts, compressors [4], and are widely used to protect surfaces against corrosion and wear in the petrochemical, aerospace and food industries [5,6] and also in automotive and electronics industry [7].…”
Section: Introductionmentioning
confidence: 99%